2021
DOI: 10.1371/journal.pone.0248322
|View full text |Cite
|
Sign up to set email alerts
|

Ear wound healing in MRL/MpJ mice is associated with gut microbiome composition and is transferable to non-healer mice via microbiome transplantation

Abstract: Objective Adult elastic cartilage has limited repair capacity. MRL/MpJ (MRL) mice, by contrast, are capable of spontaneously healing ear punctures. This study was undertaken to characterize microbiome differences between healer and non-healer mice and to evaluate whether this healing phenotype can be transferred via gut microbiome transplantation. Methods We orally transplanted C57BL/6J (B6) mice with MRL/MpJ cecal contents at weaning and as adults (n = 57) and measured ear hole closure 4 weeks after a 2.0mm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 69 publications
(78 reference statements)
3
12
0
Order By: Relevance
“…In healer MRL mice, Velasco et al showed that healing of ear punch wounds is linked with the gut microbiome. Excitingly, this healing ability could be transferred to non‐healer mice by faecal transplant 15 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In healer MRL mice, Velasco et al showed that healing of ear punch wounds is linked with the gut microbiome. Excitingly, this healing ability could be transferred to non‐healer mice by faecal transplant 15 …”
Section: Discussionmentioning
confidence: 99%
“…Excitingly, this healing ability could be transferred to non-healer mice by faecal transplant. 15 4.4 | TLR4 signalling may contribute to the regenerative response in tadpole tails TLR4 signalling is not as well characterised in amphibia as it is in mammals. Recent work in urodele amphibia (axolotl) showed that inflammatory responses to PAMP ligands, such as LPS, through TLRs, are conserved.…”
Section: Commensal Microbiota May Have a Critical Role In Regeneratio...mentioning
confidence: 99%
See 2 more Smart Citations
“…Several reviews indicate an impact of gut microbiota on development of SSI, but valid data of clinical trials focusing on the relation between SSI and gut microbiota are widely lacking [29,81,104]. Velasco et al showed an improvement of ear wound healing in mice after gut microbiome transplantation [105]. They found a positive correlation of wound healing with the phylum Firmicutes (order Clostridiales and Lactobacillales) and a negative correlation with the phylum Verrucomicrobia and Proteobacteria (order Burkholderiales).…”
Section: Research Question 3: the Relation Between The Gut Microbiota And The Development Of Surgical Site Infectionsmentioning
confidence: 99%